Paraxanthine safety and comparison to caffeine - Szlapinski, Sandra K.; Charrette, Andrew; Guthrie, Najla; Hilmas, Corey J. (Frontiers in Toxicology, 2023)
Introduction: Caffeine, one of the most ubiquitous ingredients found in beverages and other ingested food products, has a long history of safe use. As a member of the methylxanthine class of stimulants, caffeine is not devoid of unwanted side effects at any serving level. Caffeine safety has been the subject of a safety workshop by FDA and the Institute of Medicine in the past decade. Thus, investigation into an alternate stimulant with similar pharmacology but improved safety is warranted. Paraxanthine (1,7-dimethylxanthine) is the predominant metabolite of caffeine in humans with similar stimulant properties. The few toxicity studies that are available for paraxanthine suggest that the molecule is relatively safe, although thorough characterization of its safety is required prior to widespread incorporation into foods/beverages. Methods: The aim of this study was to evaluate the toxicity of paraxanthine (Rarebird, Inc.) relative to caffeine through a battery of toxicological studies conducted in accordance with international guidelines. These studies evaluated the potential mutagenicity (bacterial reverse mutation, in vitro mammalian chromosomal aberration), genetic toxicity (in vitro mammalian cell gene mutation) and acute, sub-acute and sub-chronic oral toxicity of paraxanthine in Sprague Dawley rats. Results/Discussion: There was no evidence of genetic toxicity or mutagenicity in the in vitro studies. An acute oral LD50 of 829.20 mg/kg body weight (bw) was established. There was no mortality or treatment-related adverse effects in the 14-day repeat dose oral toxicity study, wherein rats received low, mid, or high doses of paraxanthine (50, 100, or 150 mg/kg bw, n = 5 rats/sex/group). The same findings were observed in the subchronic repeat-dose 90-day oral toxicity study at daily doses of paraxanthine of 100, 150, or 185 mg/kg bw which were compared to caffeine at 150 or 185 mg/kg bw (n = 10 animals/sex/group). However, mortality was reported in two animals in the high dose caffeine-treated animals. Therefore, the no observed adverse effect level (NOAEL) from the 90-day study was determined to be 150 mg/kg bw for caffeine and 185 mg/kg bw for paraxanthine for both male and female Sprague Dawley rats. These findings may suggest that paraxanthine could be a safer alternative to caffeine in humans.